2023
DOI: 10.1039/d2se01389d
|View full text |Cite
|
Sign up to set email alerts
|

Defect engineering in the MA2Z4 monolayer family for enhancing the hydrogen evolution reaction: first-principles calculations

Abstract: Water electrolysis is a sustainable and clean method to produce hydrogen fuel via hydrogen evolution reaction (HER). Using effective and low-cost electrocatalysts for HER to substitute expensive noble metals is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…32 The generalized gradient approximation (GGA) functional with the parametrization of Perdew-Burke-Ernzerhof (PBE) was employed to describe the exchange-correlation term, 33,34 which has been used to investigate the electronic properties of a wide variety of materials for different applications. [35][36][37][38] The PAMAM dendrimer was modelled by three geometries with different levels of complexity, as represented in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…32 The generalized gradient approximation (GGA) functional with the parametrization of Perdew-Burke-Ernzerhof (PBE) was employed to describe the exchange-correlation term, 33,34 which has been used to investigate the electronic properties of a wide variety of materials for different applications. [35][36][37][38] The PAMAM dendrimer was modelled by three geometries with different levels of complexity, as represented in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…27 It was shown that due to the suitable band gap (1.42 eV), a high absorption coefficient, and spectroscopic limited maximum efficiency the MoGe 2 N 4 compound can be used for photovoltaic application. 28,29 A group of MA 2 Z 4 family members, [30][31][32][33][34][35] heterojunctions based on them, [36][37][38][39][40][41] single atom doped 42 and defective 43 MA 2 Z 4 monolayers are predicted to be highly efficient for the hydrogen evolution reaction (HER) and, thus, can be used as possible catalytic materials for the production of green hydrogen. It has been shown that stable Janus structures can be produced from the MA 2 Z 4 family, for example MSiGeN 4 (M = Zr and Hf) 44 and MnSbBiTe 4 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Jia et al designed defective MA 2 Z 4 monolayers as 2D electrocatalysts for hydrogen evolution reaction (HER) and investigated the stability, electronic characteristics, and catalytic activity. Their results expressed that, in comparison to the pristine MA 2 Z 4 material, vacancy regulation at the outer Z atom could obviously increase the catalytic activity for the HER [26]. A class of 2D Janus WSiGeZ 4 materials was also introduced by Liu et al, they discovered that the photocatalytic and electrical properties of the WSiGeZ 4 were sensitive to change in the Z elements, and applying the biaxial strains could be modulated the photocatalytic and optical properties of the materials [27].…”
Section: Introductionmentioning
confidence: 99%